1995
DOI: 10.1002/maco.19950461206
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum as a material of construction for the chemical processing industry – A critical survey

Abstract: Dedicated to Professor Dr. Elsbeth Wendler-Kalsch on the occasion of her 60th birthdayMaterials selection is based on safety and economic considerations; the least expensive material securely withstanding service conditions for a required service time is chosen. For the integrity of equipment in the CPI chemical resistance is an essential factor. Of all metallic materials used for CPI equipment, tantalum is second to none regarding chemical inertness, comparing only to resistance properties of the nonmetals gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Besides, tantalum is used in chemical processing equipment because it is extremely stable. The reason for this is the formation of a thin amorphous tantalum oxide layer at the surface, which is chemically very inert [8]. Deposition of tantalum and its oxides and nitrides can be done by physical vapour deposition, by chemical vapour deposition, or by thermal oxidation.…”
mentioning
confidence: 99%
“…Besides, tantalum is used in chemical processing equipment because it is extremely stable. The reason for this is the formation of a thin amorphous tantalum oxide layer at the surface, which is chemically very inert [8]. Deposition of tantalum and its oxides and nitrides can be done by physical vapour deposition, by chemical vapour deposition, or by thermal oxidation.…”
mentioning
confidence: 99%
“…Owing to the corrosiveness of HCl, process intensification using high-temperature/high-pressure conditions is a nontrivial affair, using either batch or continuous flow processing. The most common choice for processing highly corrosive concentrated HCl at elevated temperatures in industry are high performance Ni-based (Hastelloy C-276, Hastelloy B-3), or Ta-based alloys (Ta, Ultra 76), in addition to certain types of ceramic materials (for example SiC) . Since the chemical resistance of these materials toward aqueous concentrated HCl in an elevated temperature and pressure regime has not been fully documented, and in addition since these materials are exceedingly expensive and difficult to manufacture, we have opted to use standard glass microreactors for our laboratory-scale investigations (see below).…”
Section: Resultsmentioning
confidence: 99%
“…In previous investigations, it has been constantly reported that physical vapor deposited (PVD) coatings are characterized by possessing different types of defects such as holes, cracks, and impurities, among others, due to their chemical composition, structure, and deposition parameters. In aggressive environments, these defects can be direct paths to the substrate, thus causing localized corrosion and a decrease in protective efficiency [55]. The energy with which the material strikes the growing film during its deposition can also influence the density of these defects through the variation of the energy with which the ions reach the surface of the substrate, which could influence the atomic distribution surface and generate changes in the corrosive behavior of coatings.…”
Section: Corrosion Resistance Analysismentioning
confidence: 99%